Análise geoespacial da Comunidade Quilombola de Umarizal - Baião/PA - SILVA, Luiz Sérgio Gomes da (2022)
The present study was carried out in the remaining quilombola Umarizal community, located in the municipality of Baião state of Pará and aimed to detect possible changes in its territory and in the socioeconomic and cultural dimensions of that community in the period of 20 years (2001-2021). The methodology used to obtain data that supported this Course Completion Work (CBT) involved bibliographic consultations, field research with questionnaire application, oral reports, on-site observations and use of Geoprocessing techniques. Subsequently, the SOCIOECONOMIC and Environmental Regressive Regressive Analysis was applied to evaluate the above-mentioned dimensions. After processing and analysis of the obtained data, it was possible to verify changes in the physiognomy of the territory, with emphasis on the expansion of the residential nucleus. There was a positive change in socioeconomic status, however, the traditional culture declined. It is concluded that the territory, as well as the socioeconomic and cultural dimensions of the quilombola community, underwent changes in the period studied.